2016
DOI: 10.1093/humrep/dew266
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of unplanned pregnancy ending in birth, associated factors, and health outcomes

Abstract: Not applicable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
74
8
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(115 citation statements)
references
References 40 publications
13
74
8
8
Order By: Relevance
“…In terms of education level, the results of other studies have shown that women with lower education levels were more likely to experience unintended pregnancy (7,14,33). In this regard, it seems that the changes in FP policies can be a reason for increased pregnancy among less-educated women in households from lower socioeconomic groups, who had a higher risk of experiencing unintended pregnancy than others and compared to the previous period of FPP implementation.…”
Section: Discussionmentioning
confidence: 95%
“…In terms of education level, the results of other studies have shown that women with lower education levels were more likely to experience unintended pregnancy (7,14,33). In this regard, it seems that the changes in FP policies can be a reason for increased pregnancy among less-educated women in households from lower socioeconomic groups, who had a higher risk of experiencing unintended pregnancy than others and compared to the previous period of FPP implementation.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, in the USA, pregnant women with unintended pregnancies were associated with cigarette smoking and lack of adequate vitamins (62). In Belgium, inadequate folic acid or vitamin intake and a lower number of prenatal clinic visits were significantly associated with an unplanned pregnancy (17).…”
Section: Discussionmentioning
confidence: 99%
“…This may also invariably be due to an earlier age of starting sexual life and the increasingly popular concept of small family size (14). Other potentially associated factors are teenage pregnancy (15,16), first pregnancy as well as high parity (17), low educational status of the mother or father (18), poverty, lack of social support, Gender Based Violence (GBV), physical and sexual violence (19) and low birth interval (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Наявність великої розпластаної плаценти або декількох плацент нерідко є причиною низького розташування і передлежання плаценти. Значно частіше, ніж при одноплідній вагітності, спостерігаються такі ускладнення, як кровотечі під час вагітності та в пологах, аномалії пологової діяльності [12].…”
unclassified